A case of Ogilvie’s syndrome associated with electrolyte imbalance in a healthy individual - Manappallil, Robin George; Suresh, Chinganthara Cleetus; Kadengil, Dilshad; Thomas, Prasad; Jayaraj, Jishnu (Asian Journal of Medical Sciences, 2017)
Ogilvie’s syndrome or acute colonic pseudo-obstruction is a rare and acquired disorder characterized by significant dilatation of the colon. The condition is mainly seen in hospitalized patients with medical or surgical problems. We report the case of a middle aged healthy lady who presented with Ogilvie’s syndrome with associated electrolyte imbalance in the form of hypokalemia and hypomagnesemia. Ogilvie’s syndrome itself is a rare condition, and to the best of our knowledge has not been reported among healthy individuals yet. Asian Journal of Medical Sciences Vol.8(1) 2017 100-103